2018
DOI: 10.1002/lsm.23038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of noninvasive multisource radiofrequency treatment on periorbital rhytids using an imaging device

Abstract: Objective: To evaluate the efficacy of the multisource radiofrequency in periorbital wrinkles treatment using a VISIA imager. Methods: This is a prospective cohort study involving 30 sites in 15 patients. Inclusion criteria: healthy subjects with periorbital wrinkles. Patients underwent five treatment sessions for each site using multisource radiofrequency. VISIA imager was used before and after each treatment, and in 12-week follow-up. The wrinkle scores were calculated and compared between baseline and 12wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Other studies have reported discrepancies in wrinkle analysis between VISIA and other tools. [14][15][16][17][18] Kwon et al 16 noted that the investigator global assessment (IGA) detected changes in wrinkles earlier than VISIA following treatment with a microneedle monopolar radiofrequency device. However, when a significant change was detected by VISIA it was more sensitive than the IGA in detecting differences between the two types of needles used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported discrepancies in wrinkle analysis between VISIA and other tools. [14][15][16][17][18] Kwon et al 16 noted that the investigator global assessment (IGA) detected changes in wrinkles earlier than VISIA following treatment with a microneedle monopolar radiofrequency device. However, when a significant change was detected by VISIA it was more sensitive than the IGA in detecting differences between the two types of needles used.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported discrepancies in wrinkle analysis between VISIA and other tools. [14][15][16][17][18] Kwon et al 16 Interestingly, in a recent comparison between VISIA and Image-Pro Plus (Media Cybernetics Inc.), the sensitivity of the software was found to vary according to skin sites and VISIA was more sensitive for wrinkle assessment of the forehead. 18 In our quantitative wrinkle analysis, we found least improvement in wrinkle thickness but greatest improvement in wrinkle area in the front face (including forehead).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are safe in all skin types. 15 Non-insulated microneedle RF (NIMRF) allows non-thermal penetration of the epidermis, followed by RF full coagulation and an adequate volume of dermal heating, which induces neocollagenesis. 16,17 In recent years, NIMFR has been used to treat atrophic scars and face wrinkles.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency (RF) devices work by emitting an RF current to the target tissue, which is then converted to heat and causes collagen denaturation and neocollagenesis. These effects are safe in all skin types . Non‐insulated microneedle RF (NIMRF) allows non‐thermal penetration of the epidermis, followed by RF full coagulation and an adequate volume of dermal heating, which induces neocollagenesis .…”
Section: Introductionmentioning
confidence: 99%
“…The VISIA Skin Analysis System has been widely used in many dermatological and aesthetic settings. The system is used for the assessment of pores, pigmentation, redness, texture, and wrinkles [21–23]. Recent studies have been used to help assess outcomes of treatments for photo‐aging skin, erythema from acne and changes in periocular wrinkles post non‐ablative fractional laser treatment [24–26].…”
Section: Discussionmentioning
confidence: 99%